Women’s Reactions to Men’s Patriarchal Oppressions in Selected Ghanaian Male and Female Novels - Theophile Houndjo; Akinola Monday Allagbe (European Scientific Journal, ESJ, 2018)
Social imbalances between men and women are the bedrock of injustices women encounter in the world, particularly in African societies. Patriarchy is identified by womanist and feminist scholars as one of the social practices that give men more privilege and maintain women in peripheral roles. This article examines how female characters in African patriarchal settings of two Ghanaian male and female novels, Asare Adei’s A Beautiful Daughter (2012) and Amma Darko’s The Housemaid (1998) have been able to face/cope with men’s oppressions through womanist and radical feminist theories. The findings have revealed that majority of the female characters are empowered economically and socially in the male and female fictional texts, and this has enabled them to combat men’s patriarchal oppressions. The female characters’ reactions vary from one another. Some of them made use of pacific ways such as dialogue, feminine solidarity or sisterhood in their attempts to address men’s patriarchal oppressions, while others have made use of violence against men and children in their quest for justice and equality.